2020
DOI: 10.21203/rs.3.rs-33962/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Toxicity of orally administered food-grade titanium dioxide nanoparticles

Abstract: Background The International Agency for Research on Cancer classified as a Group B carcinogen inhaled titanium dioxide (TiO 2 ) nanoparticles, and France banned the application of TiO 2 nanoparticles as a food additive based on the insufficient oral toxicity data. However, there still remains controversial due to the insufficient evidence for its safety. Here, we explored the toxicity of food-grade TiO 2 nanoparticles (hereafter, E171) in vivo and in vitro . Methods We investigated the subchronic toxic re… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(6 citation statements)
references
References 1 publication
0
6
0
Order By: Relevance
“…In mice, no adverse effects associated with general toxicity were observed up to 1,000 mg E 171/kg bw per day, the highest dose tested, for dosing durations up to 90 days (Han et al., 2020a, scoring 2 for NSC). Also in rats, no adverse effects associated with general toxicity were observed in the EOGRT study with E 171 (Documentation provided to EFSA No 1) (scoring 4 for NSC) at doses up to 1,000 mg/kg bw per day (Section 4.2).…”
Section: Discussionmentioning
confidence: 97%
See 4 more Smart Citations
“…In mice, no adverse effects associated with general toxicity were observed up to 1,000 mg E 171/kg bw per day, the highest dose tested, for dosing durations up to 90 days (Han et al., 2020a, scoring 2 for NSC). Also in rats, no adverse effects associated with general toxicity were observed in the EOGRT study with E 171 (Documentation provided to EFSA No 1) (scoring 4 for NSC) at doses up to 1,000 mg/kg bw per day (Section 4.2).…”
Section: Discussionmentioning
confidence: 97%
“…In the Han et al. (2020a) 90‐day study, effects on GM‐CSF and IgM and were observed following exposure to E 171, however the Panel noted the lack of a dose response, the magnitude of the effect was small that did not allow a firm conclusion given the natural variability in the parameters measured. It should be noted that in three single dose level studies with E 171 inflammatory effects were noted at lower doses, i.e.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations